METODE DAKWAH UNTUK GENERASI MILENIAL - Mujahadah, Siti (Jurnal Dakwah Tabligh, 2021)
Da’wah method is one element of da’wah that has an important and strategic role for the success of da’wah. The method of da’wah always experiences development in accordance with the development of the situation and the times. In preaching, there are many methods that can be applied by a preacher in conveying the message of preaching. Dai must use appropriate methods with the objectives of da’wah, so that da’wah can achieve success. The millennial era is an era where technology is developing so rapidly, making it easier for people to get information from various places in the world. This millennial era can be said as the golden period of the millennial generation. The millennial generation in Indonesia is very addicted to the internet, in this way, to make it easier for the preacher to convey the message of preaching must follow the development of existing technology. Submission of da’wah messages through social media is very supportive of the millennial generation.